Transformation From Schottky to Ohmic Contact at High Temperature in Diamond Schottky Barrier Diode - Cui, Shuning (Transactions on Computer Science and Intelligent Systems Research, 2024)
Relations between Schottky contact and ohmic contact in diamond Schottky diode is attentively studied. Whether the metal-semiconductor contact forms metal carbide at high temperature on the interface of p-diamond is showed to determine the character of the contact. Formation of carbide and/or intermixing of metal and p-diamond at elevated temperature are believed to lower the Schottky barrier height and make Schottky contact “ohimicize” in a certain extent. This transformation can be advantageous for fabricating ideal ohmic contact, especially when boosted by annealing, but it can also be detrimental to maintaining high-quality Schottky contact at higher temperature. This suggests general criteria for identifying potential candidates for the two types of contact. Oxide and/or surface intermixture formed by metal and Oxygen-Terminals (OTs) on p-diamond, however, can resist the transformation trend at high temperature, thereby leading to better thermal stability. Nevertheless, the desorption of OTs at certain temperature may lead to re-reaction between metal and carbon, thus lowering the barrier again. Luckily, this temperature limit for certain metal is usually higher than the operating high-enough temperature and has less to do with the thermal stability and effectiveness of the functioning diode. Finally, careful selection of metal materials combined with adjustment of Schottky barrier height through high temperature can help fabricate desirable, robust and more economic diamond Schottky diode working at required higher temperature. Similar phenomenon may be observed for non-diamond Schottky diode as well and further researches can be conducted.